Gender Equality in Indonesia’s Legal System: Progress or Stagnation? - Kumaar, Sahid; Muqorrobin, Ikram; Al-Faroq, Fathan (Universitas Negeri Semarang, 2025)
This study examines the progress of gender equality within Indonesia's legal system, focusing on whether recent reforms have achieved meaningful change or if they merely represent stagnation. Despite legal advancements, such as the ratification of international conventions and national laws aimed at promoting gender equality, women in Indonesia continue to face significant challenges, including discrimination, violence, and limited access to opportunities in various sectors. This research investigates the alignment of Indonesia’s legal framework with gender equality principles, analyzing legislative reforms, their implementation, and the societal and institutional barriers that hinder their effectiveness. Key findings highlight a persistent gap between legal reforms and societal practices, often compounded by traditional gender norms and weak enforcement mechanisms. While there have been notable improvements in areas such as women’s political participation and domestic violence protection, other issues, including workplace discrimination and the underrepresentation of women in leadership positions, remain inadequately addressed. The novelty of this study lies in its comprehensive evaluation of both legal reforms and their real-world impact, presenting a nuanced understanding of gender equality in Indonesia. Given the country’s dynamic social and political landscape, this research is urgent for informing policymakers, activists, and legal practitioners about the gaps that remain and the necessary steps to ensure that gender equality is not just a legal aspiration but a lived reality. This study contributes to the broader discourse on gender justice by offering concrete recommendations for enhancing the effectiveness of legal reforms in promoting gender equality in Indonesia.